Surface-activity-free high-performance film and preparation method thereof

Through semi-continuous Pickering emulsion polymerization method, small particle size and high solids silica-polymer microspheres were prepared, which solved the hydrophilicity problem under the influence of surfactants and achieved high performance with high water resistance and mechanical strength. The film is used to regulate the film's performance through the dropping time of monomer.

CN119219867AActive Publication Date: 2024-12-31JIANGNAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411396261.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

In the existing preparation methods for aqueous dispersions, surfactants are required, which leads to an increase in hydrophilicity of latex particles when forming films, making it difficult to achieve films with high water resistance and mechanical strength.

Method used

Using semi-continuous Pickering emulsion polymerization method, small-particle size, high-solid silica-polymer microspheres are prepared by adjusting pH and monomer dropping time. They are directly used for the Film formation.

Benefits of technology

A film with high transparency, good mechanical properties and high water resistance is obtained, and the transparency and mechanical properties of the film can be adjusted by regulating the dropping time of the monomer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219867A_ABST
    Figure CN119219867A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water-resistant thin film preparation, in particular to a method for preparing a high-performance water-resistant thin film through Pickering emulsion polymerization. Comprising the following steps: (1) preparing a film-forming emulsion by using semi-continuous Pickering emulsion polymerization; and (2) neutralizing the film-forming emulsion, and pouring the film-forming emulsion into a mold to form a film. According to the invention, the silicon dioxide-polymer microspheres with smaller particle size and higher solid content can be obtained without using a surfactant and adding an auxiliary comonomer or using a cationic initiator, and the silicon dioxide-polymer microspheres are used for film formation. The prepared film has good transparency and good mechanical properties. The particle size of the generated latex particles is regulated and controlled by regulating and controlling the dropwise adding time of the monomer, so that the distribution of silicon dioxide in the film is regulated and controlled, and the performance of the obtained film also changes along with the regulation and control. The high-performance film has potential application in the field of water-based anticorrosive paint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of film preparation, and in particular to a method for preparing a high-performance polymer film. Background Art

[0002] Waterborne dispersions are increasingly replacing solvent-based dispersions in the fields of coatings, adhesives, etc. due to their low VOC emissions and environmental friendliness. Currently, common waterborne dispersions are mainly synthesized by secondary dispersion or emulsion polymerization, but both methods have certain limitations. The former inevitably requires the use of some solvents during the polymerization process, while the latter requires a certain amount of surfactants to stabilize the generated emulsion, and the presence of surfactants will affect the film-forming properties of latex particles.

[0003] During the film-forming process of latex particles, the surfactant will migrate upward and a large number of small molecule surfactants will be enriched on the surface. The hydrophilicity of the small molecule surfactants will make the surface of the film also have a certain degree of hydrophilicity, which is not conducive to the use of the film in places that require high water resistance.

[0004] Inorganic particles have the ability to stabilize oil droplets in water, which is called Pickering stabilization. Subsequently, Pickering emulsion polymerization with inorganic particles as stabilizers began to develop. The first developed Pickering emulsion polymerization is to promote the adsorption of silica to the generated latex particles by modifying inorganic particles such as silica, copolymerizing polymer monomers with opposite charges to silica, and using cationic azo initiators. Subsequent studies have shown that when using the more hydrophilic monomer MMA, using KPS as an initiator can promote the adsorption of unmodified silica to the surface of latex particles through van der Waals forces. However, the particle size of the organic-inorganic hybrid particles prepared by this method is large, and it is difficult to achieve a high solid content. And film-forming latex particles with larger particle sizes are not conducive to film formation.

[0005] Therefore, it is necessary to develop a high-performance film that does not require the addition of surfactants, has high water resistance, and has good mechanical strength. Summary of the invention

[0006] In order to solve the above problems, the present application provides a method for preparing a small-particle-size, high-solid-content Pickering emulsion and using it for film formation. Hybrid microspheres with smaller particle sizes can be obtained without adding auxiliary copolymer monomers or cationic azo initiators, and the transparency and mechanical properties of the film can be changed by adjusting the monomer addition time.

[0007] A first aspect of the present invention provides a method for preparing a high-performance polymer film, comprising the following steps:

[0008] (1) using semi-continuous Pickering emulsion polymerization to prepare film-forming emulsions;

[0009] (2) After neutralizing the film-forming emulsion, pour it into a mold to form a film.

[0010] Furthermore, the step (1) specifically includes the following steps: S1, S2, S3;

[0011] S1. Prepare reaction solution: prepare silicon dioxide aqueous dispersion and adjust pH to between 3-6;

[0012] S2, preparing an initiator solution: dissolving an initiator in water to prepare an initiator solution;

[0013] S3, preparing a film-forming emulsion: adding the first component cross-linking monomer to the reaction solution after adjusting the pH, then slowly dropping the initiator solution and the monomer into the reaction solution after heating and nitrogen removal, and continuing the reaction to obtain a film-forming emulsion;

[0014] In some preferred embodiments, step S1 further comprises the step of passing nitrogen through the reaction container to remove residual oxygen.

[0015] Furthermore, step (2) includes S4, S4: adjusting the pH of the film-forming emulsion obtained in step S3, adding the second component cross-linking monomer and pouring it into a mold to form a film.

[0016] Furthermore, in step S1, the reaction solution contains 25-88 parts of solvent water and 1-10 parts of silicon dioxide in parts by mass.

[0017] In some preferred embodiments, in step S1, the amount of silicon dioxide added is 1%-10% of the total mass of water and silicon dioxide.

[0018] Furthermore, the initiator includes but is not limited to potassium persulfate, ammonium persulfate, azobisisobutylamidine hydrochloride, azobisisobutyronitrile, and any one or a combination of two or more thereof;

[0019] Furthermore, the first component cross-linking monomer is diacetone acrylamide; the amount of the first component cross-linking monomer is 2.2%-11% of the monomer mass;

[0020] Furthermore, the second component cross-linking monomer is adipic acid dihydrazide; the amount of the second component cross-linking monomer is 1.1%-5% of the monomer mass;

[0021] Furthermore, the monomer includes but is not limited to any one or a combination of two or more of methyl methacrylate, ethyl methacrylate, n-butyl acrylate, n-ethyl acrylate, isobutyl acrylate, etc.;

[0022] Further, in step S3, the monomer addition time is 0 min-180 min;

[0023] In some preferred embodiments, in step S3, the monomer addition time is 0 min-60 min; more preferably 30 min-60 min;

[0024] Further, in step S3, the initiator is added dropwise for 0 min to 180 min;

[0025] In some preferred embodiments, in step S3, the initiator is added for a period of 0 min to 60 min.

[0026] Furthermore, in step S3, the particle size of the emulsion finally obtained should be between 100 nm and 300 nm.

[0027] In some embodiments, in step S3, the system reaction temperature can be any temperature between 50-80°C;

[0028] In one embodiment, the final solid content of the emulsion prepared in step S3 is 10%-50%; preferably 10%-40%;

[0029] Further, in step S4, the pH is adjusted to a value between 8 and 9;

[0030] Furthermore, in step S4, the film forming temperature is between 60°C and 80°C.

[0031] Further, in step S1, the silica particle size is 10-30 nm;

[0032] Further, the amount of monomer added in step S3 is 10-30% of the total mass of the emulsion;

[0033] In some preferred embodiments, the monomer is methyl methacrylate monomer, and the amount added is 10-30% of the total mass of the solution;

[0034] Furthermore, the amount of the initiator added is 1%-3% of the total mass of the solution.

[0035] In some preferred embodiments, step S3: add the first component cross-linking monomer to the S1 system and then heat it to 70° C., then drop methyl methacrylate monomer and initiator into the system and react for 12 hours to obtain a polymer emulsion.

[0036] In some preferred embodiments, step S4 specifically includes the following steps: adding ammonia water to the film-forming emulsion to adjust the pH, then adding a second cross-linking monomer, and then pouring the film-forming emulsion into a polytetrafluoroethylene mold to form a film.

[0037] The second aspect of the present invention provides a high-performance film produced by the method for producing the high-performance polymer film.

[0038] The third aspect of the present invention provides a method for adjusting the transparency and mechanical properties of the high-performance film. In step S3, the mechanical properties and transparency of the final film are regulated by adjusting the monomer drop addition time.

[0039] Beneficial effects: Compared with the prior art, the present invention has the following characteristics and beneficial effects:

[0040] The present invention prepares hybrid microspheres through semi-continuous Pickering emulsion polymerization, and silicon dioxide-polymer microspheres with smaller particle size and higher solid content can be obtained and used for film formation without using surfactants, adding auxiliary comonomers or using cationic initiators; the prepared film has good transparency, good mechanical properties and water resistance.

[0041] The present invention also provides a method for regulating film-forming properties, and the mechanical properties and transparency of the final film can be regulated by adjusting the dropping time of the monomer and the initiator. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Digital photos of films prepared in Examples and Comparative Examples;

[0043] Figure 2 The cross-sectional scanning electron microscope characterization images of the films prepared in the examples and comparative examples;

[0044] Figure 3 is the transmittance of the films prepared in the examples and comparative examples;

[0045] Figure 4 1. The stress-strain curves of the films prepared in the embodiments and comparative examples;

[0046] Figure 5 The 24h and 7day water absorption curves of the films prepared in the examples and comparative examples are shown. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with the accompanying drawings and Examples. According to the following examples, the present invention can be better understood. However, it is easy for those skilled in the art to understand that the specific material ratios, process conditions and results described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0048] Example 1: Preparation of high performance thin films

[0049] This example describes in detail a method for preparing a polymer film.

[0050] The raw materials are as follows: diacetone acrylamide (DAAM), adipic acid dihydrazide (ADH), methyl methacrylate (MMA), n-butyl acrylate (BA), Ludox TM-40 (silicon dioxide aqueous dispersion), potassium persulfate (KPS), dilute hydrochloric acid, and water.

[0051] The specific preparation process is as follows:

[0052] 1. Add 20g ultrapure water and 25g Ludox TM-40 to a three-necked flask and stir at 300rpm to mix evenly. Add dilute hydrochloric acid to adjust the pH to 5.5, then pass nitrogen for 30min to remove oxygen, heat to 70℃, directly add 0.44g diacetone acrylamide, 10g methyl methacrylate and 10g n-butyl acrylate and 0.2g initiator KPS dissolved in 10g water and react for 12h.

[0053] After the reaction, a polymer microsphere emulsion was obtained, and ammonia water was added to adjust the pH to about 8-9, and then 0.22 g of adipic acid dihydrazide was added, stirred, and poured into a polytetrafluoroethylene mold to form a film at 70 degrees Celsius for 24 hours.

[0054] Example 2: Preparation of high-performance film (monomer addition time 30 min)

[0055] This example describes in detail a method for preparing a polymer microfilm.

[0056] The raw materials are as follows: diacetone acrylamide (DAAM), adipic acid dihydrazide (ADH), methyl methacrylate (MMA), n-butyl acrylate (BA), Ludox TM-40 (silicon dioxide aqueous dispersion), potassium persulfate (KPS), dilute hydrochloric acid, and water.

[0057] The specific preparation process is as follows:

[0058] 1. Add 20g ultrapure water and 25g Ludox TM-40 to a three-necked flask and stir at 300rpm to mix evenly. Add dilute hydrochloric acid to adjust the pH to 5.5, then pass nitrogen for 30 minutes to remove oxygen, heat to 70°C, directly add 0.44g diacetone acrylamide, then slowly add 10g methyl methacrylate and 10g n-butyl acrylate and 0.2g initiator KPS dissolved in 10g water over 30 minutes and react for 12 hours.

[0059] After the reaction, a polymer microsphere emulsion was obtained, and ammonia water was added to adjust the pH to about 8-9, and then 0.22 g of adipic acid dihydrazide was added, stirred, and poured into a polytetrafluoroethylene mold to form a film at 70 degrees Celsius for 24 hours.

[0060] Example 3: Preparation of high-performance film (monomer addition time 60 min)

[0061] This example describes in detail a method for preparing a polymer film.

[0062] The raw materials are as follows: diacetone acrylamide (DAAM), adipic acid dihydrazide (ADH), methyl methacrylate (MMA), n-butyl acrylate (BA), Ludox TM-40 (silicon dioxide aqueous dispersion), potassium persulfate (KPS), dilute hydrochloric acid, and water.

[0063] The specific preparation process is as follows:

[0064] 1. Add 20g ultrapure water and 25g Ludox TM-40 to a three-necked flask and stir at 300rpm to mix evenly. Add dilute hydrochloric acid to adjust the pH to 5.5, then pass nitrogen for 30 minutes to remove oxygen, heat to 70°C, directly add 0.44g diacetone acrylamide, then slowly add 10g methyl methacrylate and 10g n-butyl acrylate and 0.2g initiator KPS dissolved in 10g water over 60 minutes and react for 12 hours.

[0065] After the reaction, a polymer microsphere emulsion was obtained, and ammonia water was added to adjust the pH to about 8-9, and then 0.22 g of adipic acid dihydrazide was added, stirred, and poured into a polytetrafluoroethylene mold to form a film at 70 degrees Celsius for 24 hours.

[0066] Example 4: Preparation of high-performance film (monomer addition time 90 min)

[0067] This example describes in detail a method for preparing a polymer film.

[0068] The raw materials are as follows: diacetone acrylamide (DAAM), adipic acid dihydrazide (ADH), methyl methacrylate (MMA), n-butyl acrylate (BA), Ludox TM-40 (silicon dioxide aqueous dispersion), potassium persulfate (KPS), dilute hydrochloric acid, and water.

[0069] The specific preparation process is as follows:

[0070] 1. Add 20g ultrapure water and 25g Ludox TM-40 to a three-necked flask and stir at 300rpm to mix evenly. Add dilute hydrochloric acid to adjust the pH to 5.5, then pass nitrogen for 30 minutes to remove oxygen, heat to 70°C, directly add 0.44g diacetone acrylamide, then slowly add 10g methyl methacrylate and 10g n-butyl acrylate and 0.2g initiator KPS dissolved in 10g water over 90 minutes and react for 12 hours.

[0071] After the reaction, a polymer microsphere emulsion was obtained, and ammonia water was added to adjust the pH to about 8-9, and then 0.22 g of adipic acid dihydrazide was added, stirred, and poured into a polytetrafluoroethylene mold to form a film at 70 degrees Celsius for 24 hours.

[0072] Comparative Example 1: Preparation of high-performance film (emulsion polymerization containing surfactant)

[0073] This example describes in detail a method for preparing a polymer film.

[0074] The raw materials are as follows: diacetone acrylamide (DAAM), adipic acid dihydrazide (ADH), methyl methacrylate (MMA), n-butyl acrylate (BA), sodium dodecyl sulfate (SDS), potassium persulfate (KPS), dilute hydrochloric acid, and water.

[0075] The specific preparation process is as follows:

[0076] 1. Add 30g ultrapure water and 0.3g sodium dodecyl sulfate to a three-necked flask and stir at 300rpm to mix evenly. Add dilute hydrochloric acid to adjust the pH to 5.5, then pass nitrogen for 30 minutes to remove oxygen, heat to 70℃, directly add 0.44g diacetone acrylamide, 10g methyl methacrylate and 10g n-butyl acrylate and 0.2g initiator KPS dissolved in 10g water and react for 12h.

[0077] After the reaction, a polymer microsphere emulsion was obtained, and ammonia water was added to adjust the pH to about 8-9, and then 0.22 g of adipic acid dihydrazide was added, stirred, and poured into a polytetrafluoroethylene mold to form a film at 70 degrees Celsius for 24 hours.

[0078] Comparative Example 2: Preparation of polymer emulsion (emulsion polymerization containing surfactant)

[0079] This example describes in detail a method for preparing a polymer film.

[0080] The raw materials are as follows: diacetone acrylamide (DAAM), adipic acid dihydrazide (ADH), methyl methacrylate (MMA), n-butyl acrylate (BA), Ludox TM-40 (silicon dioxide aqueous dispersion), potassium persulfate (KPS), dilute hydrochloric acid, water, sodium dodecyl sulfate (SDS).

[0081] The specific preparation process is as follows:

[0082] 1. Add 30g ultrapure water and 0.3g sodium dodecyl sulfate to a three-necked flask and stir at 300rpm to mix evenly. Add dilute hydrochloric acid to adjust the pH to 5.5, then pass nitrogen for 30 minutes to remove oxygen, heat to 70°C, directly add 0.44g diacetone acrylamide, 10g methyl methacrylate and 10g n-butyl acrylate and 0.2g initiator KPS dissolved in 10g water to react for 12h.

[0083] After the reaction, a polymer microsphere emulsion was obtained, and ammonia water was added to adjust the pH to about 8-9, then 0.22 g of adipic acid dihydrazide was added and stirred, and then 25.0 g of Ludox TM-40 silica aqueous dispersion was added and mixed evenly, and then poured into a polytetrafluoroethylene mold to form a film at 70 degrees Celsius for 24 hours.

[0084] Table 1 Film formation by different polymerization methods

[0085]

[0086] Test example:

[0087] Figure 1 Digital photos of films obtained by different polymerization methods; Figure 2 The following are cross-sectional SEM images of films obtained by different polymerization methods. Figure 1 As shown, it can be seen that the films prepared by traditional emulsion polymerization and Pickering emulsion polymerization with a monomer addition time of less than 60 min (Examples 1-3 and Comparative Examples 1-2) have good transparency.

[0088] The emulsion obtained by conventional emulsion polymerization was directly blended with silica sol to form a film (Comparative Example 2). The cross section of the film was characterized by SEM. A large amount of silica agglomerates Figure 2 -B causes the whitish area to produce Figure 1 -B.

[0089] When the monomer dropping time is extended to 90min, the emulsion obtained by polymerization is used for film formation, and the film cracking phenomenon generated is serious and cannot be completely removed from the mold (Example 4). The interface of the film is characterized by SEM, and it is found that silicon dioxide is more regularly concentrated in a specific area and is distributed more densely. Therefore, the reason why the film-forming performance is poor may be that in the latex particle film-forming process, the particle size of the smaller latex particles promotes the close packing between silicon dioxide, causing the movement of the polymer chain to be hindered and unable to form a uniform and complete film.

[0090] The spectrophotometer test in the visible light range was performed on Examples 1-3 and Comparative Example 1 (four groups A, C, D, and E). Figure 3 As shown, the transmittance of the four groups of films is high. Figure 2The cross sections of -A, C, D, and E also show that silicon dioxide is dispersed relatively evenly in the film, and the distribution of silicon dioxide will also affect the transmittance of the film.

[0091] The mechanical properties of the four groups of Examples 1-3 and Comparative Example 1 (Groups A, C, D, and E) were tested. Figure 4 The monomer addition time has a significant effect on the mechanical properties of the final film. When the monomer addition time increases from 0 min to 60 min, the yield stress of the film increases from 7 MPa to about 13.5 MPa, but the elongation at break decreases from 380% to 44%. The possible reason for the change in yield stress and elongation at break is the different distribution of silica, such as Figure 2 As shown in CE, as the monomer addition time increases, silica tends to be densely packed to form individual stress concentration points to strengthen the film, but it also reduces the elongation at break of the film. The film prepared by the traditional emulsion stabilized by 1% SDS (Comparative Example 1) without adding silica has good toughness but low strength and yield stress of only about 4MPa. Therefore, the emulsion film prepared by Pickering emulsion polymerization has good mechanical properties and the relationship between the strength and toughness of the generated film can be adjusted by controlling the monomer addition time.

[0092] The film prepared in this application has the advantages of low water absorption and better water resistance because no surfactant is required to participate in the polymerization process. The water absorption rate of the film formed by different polymerization methods was tested and the changes in water absorption rate within 7 days and 24 hours were compared. Figure 5 As shown. The traditional emulsion polymerization with added surfactant (Comparative Example 1) has a high water absorption rate and the water absorption rate at the final equilibrium is also very high, about 39%. Although the water absorption rate of the group in which silica is directly blended in the emulsion (Comparative Example 22) has decreased at the final equilibrium (the possible reason is that the higher the proportion of silica itself that does not absorb water, the lower the total water absorption rate). However, due to the hydrophilicity of silica and the disadvantage that blending cannot be evenly dispersed, the water absorption rate of the group directly blended with silica is very high, and a water absorption equilibrium is basically completed in about 5 hours. The film prepared in the present application has uniformly dispersed silica without the addition of a surfactant, and the equilibrium water absorption rate is low, all around 10%, and the water absorption rate is also low.

[0093] The present application prepares a high-performance water-resistant film by Pickering emulsion polymerization. Without using surfactants, adding auxiliary comonomers or using cationic initiators, silica-polymer microspheres with smaller particle size and higher solid content can be obtained and used for film formation; the prepared film has good transparency and good mechanical properties, and has high water resistance. By regulating the drop time of the monomer, the particle size of the generated latex particles is regulated, thereby regulating the distribution of silica in the film, and the performance of the obtained film will also change accordingly. This high-performance film has a high application value in the field of water-based anti-corrosion coatings.

[0094] It should be understood that the above detailed embodiments of the present disclosure are only for the purpose of illustrating or explaining the principles of the present disclosure, rather than limiting the present invention. Therefore, any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present disclosure should be included in the protection scope of the present invention. At the same time, the claims attached to the present invention are intended to cover all changes and modifications of the scope and boundaries of equivalent substitutions that fall within the scope and boundaries of the claims.

Claims

1. A method for preparing a high-performance polymer film, characterized in that: The following steps are involved: S1. Prepare reaction solution: prepare silicon dioxide aqueous dispersion and adjust pH to between 3-6; S2. Preparation of initiator solution: dissolving the initiator in water to prepare an initiator solution; S3, adding the first component cross-linking monomer to the reaction solution after adjusting the pH, then slowly dropping the initiator solution and the monomer into the reaction solution after heating and nitrogen removal, and continuing the reaction to obtain a film-forming emulsion; S4, after adjusting the pH of the film-forming emulsion obtained in step S3, add the second component cross-linking monomer and pour into a mold to form a film.

2. The method for preparing a high-performance polymer film according to claim 1, characterized in that: In step S1, the reaction solution contains 25-88 parts of solvent water and 1-10 parts of silicon dioxide in terms of mass fractions.

3. The method for preparing a high-performance polymer film according to claim 1, characterized in that: The initiator includes but is not limited to potassium persulfate, ammonium persulfate, azobisisobutylamidine hydrochloride, azobisisobutyronitrile, and any one or a combination of two or more thereof; and / or, the first component cross-linking monomer is diacetone acrylamide; And / or, the second component cross-linking monomer is adipic acid dihydrazide.

4. The method for preparing a high-performance polymer film according to claim 1, characterized in that: The monomers include but are not limited to any one or a combination of two or more of methyl methacrylate, ethyl methacrylate, styrene, n-butyl acrylate, n-ethyl acrylate, isobutyl acrylate, etc.; And / or, in step S1, the amount of silicon dioxide added is 1%-10% of the total mass of water and silicon dioxide.

5. The method for preparing a high-performance polymer film according to claim 1, characterized in that: In step S3, The monomer addition time is 0min-180min; And / or, the initiator is added dropwise for 0 min to 180 min; And / or, in step S3, the particle size of the emulsion finally obtained should be between 100 nm and 300 nm.

6. The method for preparing a high-performance polymer film according to claim 1, characterized in that: In step S4, the pH is adjusted to a value between 8 and 9; And / or, in step S4, the film forming temperature is between 60°C and 80°C.

7. The method for preparing a high-performance polymer film according to claim 1, characterized in that: In step S1, the silica particle size is 10-30 nm.

8. The method for preparing a high-performance polymer film according to claim 1, characterized in that: The amount of monomer added in step S3 is 10-30% of the total mass of the emulsion; and / or, the amount of the initiator added is 1%-3% of the total mass of the solution; And / or, the solid content of the emulsion is between 10% and 40%.

9. A high-performance film obtained by the method for preparing a high-performance polymer film according to any one of claims 1 to 8.

10. A method for adjusting the transparency and mechanical properties of the high-performance film according to any one of claims 1 to 9, characterized in that: The mechanical properties and transparency of the final film can be controlled by adjusting the monomer addition time in step S3.

Citation Information

Patent Citations

  • Method for preparing polyacrylic ester / nanoSiO2 coating printing adhesive by using Pickering emulsion polymerization method

    CN104151486A

  • Method for synthesizing Pickering-type emulsion through semi-continuous polymerization

    CN104558356A

  • Method for preparing water-resistant film without surface activity

    CN118146435A

  • Colloidosomes and porous materials by pickering emulsions

    US20220111347A1